Preserving Old Traditional Malay House: Case Study of Perak House of Rumah Kutai - Azlan, Nurul Alia; Shukri, Sharyzee Mohmad; Aziz, Adrianta; Taib, Idris (MAJ - Malaysia Architectural Journal, 2022)
“Rumah Kutai” is one of the traditional Malay houses found in Perak. It began to exist around 1817 to 1900. This ancient house is located on the banks of the Perak River in the central district, downstream Perak and Kuala Kangsar. “Rumah Kutai” is different from other traditional Malay houses in Malaysia in terms of their construction, material, spaces and ornamentation. The purpose of this study is to discuss the importance of preserving the architecture of old traditional Malay house Rumah Kutai. This research method uses a subjective methodology that includes previous literature review of articles and reports focusing on the preservation of Rumah Kutai. Another method that have been used in this study is visual observation on site to identify the causes and solutions to overcome this matter. This paper will discuss about the historical elements of architectural found in this ancient house that need to be preserved. The findings from this exploratory review will conclude that the characteristics of Rumah Kutai have the potential to conserve and preserve for the future generation.